Perancangan Infografis Tentang School Bullying Menggunakan Teknik Motion Graphic - Elfa Olivia Verdiana; Mayriensa Widya Pangestieka (Lembaga Penelitian Pengembangan dan Pengabdian Kepada Masyarakat STMIK Asia Malang, 2018)
School is the level of education that must be passed before continuing to a higher level. In a school environment bullying continues to occur, even it tends to be inherited and present in various forms that we do not realize. The case of violence in high school is the highest. So it is necessary to design an infographic media that can convey messages about school bullying at high school level using motion graphic technique. To make an infographic media it is necessary to collect data through interview method and literature study. Then the datum obtained are summarized and analyzed into important points. Stages of infographic design in the form of visualization of making object characters and background, the process of editing the addition of effects and audio until the last stage is rendering. Visual and audio elements are composed using motion graphics techniques that make the target audience understand the information contained in the infographics faster and easier. The conclusion of this infographic design that is the importance of expertise in graphic design, skills in applying effects and reproduce references about infographics. This infographic distribution is uploaded on youtube channel then the link will be shared in high school groups. In addition it will be used as a medium of learning by counseling teachers. Based on the results of product testing through questionnaires, it can be concluded that respondents responded to this infographis well and very worthy to be published.